Thalassaemia: Level of awareness among the future health care providers of Malaysia - Mainul, Haque; ATM Emdadul, Haque; Fatimah A’thirah, Puteh (2015)
Thalassaemia is a hereditary disorder which results in reduced production of haemoglobin. This disease is a major public health problem. It was reported from Malaysia in 2011 that there were nearly 4,800 registered thalassaemics. The current study was carried out to determine the level of awareness on thalassaemia among the students of Royal College of Medicine Perak, University Kuala Lumpur, Ipoh, Malaysia. This is a cross-sectional study. Students were then distributed a pretested questionnaire about thalassaemia. The results were analyzed using SPSS 17.0. Out of 281 students, 41%, 41% and 18% were pharmacy students, MBBS students and nursing students respectively. Most (72%) of the respondents were female. The mean knowledge score of nursing students was highest 5.39±1.51, out of a maximum of 7, compared to MBBS students 5.18±1.15 and pharmacy students 3.76±1.57. However, the mean attitude score of nursing (2.98±1.14) and MBBS (2.98±1.26) students was highest and same out of maximum of 5, but not much different compared to pharmacy students 2.69±1.25. Male students had higher level of knowledge on thalassaemia compared to female students. However, female students possessed better attitude when compared to male students. Only 8 students (3%) had an excellent knowledge and attitude. Most of them showed high knowledge level but lack of attitude. Although, current study population level of knowledge is not directly proportional to level of attitude. Since Malaysia is a multiracial country with different cultural and religious believe should be carefully taken into consideration for the prevention of thalassaemia.